Efeito dos microplásticos no desenvolvimento do caranguejo de água doce Dilocarcinus pagei capturados em Itacoatiara (AM), Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Microplastic particles have been found in great variety and quantity in freshwater environments around the world, including lakes and rivers, with increasing exposure to aquatic organisms. Depending on the particle size and physiological and behavioral traits of the organism, there is an opportunity for this pollutant to be ingested by invertebrate animals. Thus, the objective of this study was to evaluate the microplastic intake, retention site, fragmentation, effects caused by ingestion on Dilocarcinus pagei growth, fattening and survival. In Chapter I we introduce information on plastic production, concepts and types of microplastics, methods for analyzing this material, pollution in aquatic environments, and risks to freshwater biota including crustaceans. In Chapter II we tested the accidental microplastic ingestion of 0.5 and 1 mm and 0.5 and 1%, and checked the possibility of fragmenting these ingested particles mixed with a ration. We compared the results between adult and juvenile individuals and between males and females. We used SEM scanning electron microscopy and Raman vibrational spectroscopy to identify and confirm the microplastic used. In Chapter III we evaluated the effect of microplastic ingestion mixed with feed and macrophyte on the growth of newly hatched juveniles over a period of 90 days, and we also verified the effect on weight gain or loss of adult males and females. We conclude that ingestion can have negative effects on juvenile growth, weight gain and adult survival.
Effect of microplastics on the development of sweet water crab Dilocarcinus pagei captured in Itacoatiara (AM), Brazil
Keywords: Plásticos; Polietileno; Caranguejos; Trichodactylidae; Itacoatiara (AM); CIÊNCIAS AGRÁRIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; Crustacea; Trichodactylidae; Brachyura; Polietileno; Plástico